College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Review Exercises - Page 163: 24



Work Step by Step

Using $(a+b)(c+d)=ac+ad+bc+bd$ or the FOIL Method and using $i^2=-1$, the given expression $ (-8+2i)(-1+i) ,$ simplifies to \begin{array}{l}\require{cancel} -8(-1)-8(i)+2i(-1)+2i(i) \\\\= 8-8i-2i+2i^2 \\\\= 8-8i-2i+2(-1) \\\\= 8-8i-2i-2 \\\\= (8-2)+(-8i-2i) \\\\= 6-10i .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.